ZnO Nanoparticles: An Efficient Reagent, Simple and One-Pot Procedure for Synthesis of Highly Functionalized Dihydropyridine Derivatives - Marziyeh Khazaei; Mohammad Anary-Abbasinejad; Alireza Hassanabadi; Bahareh Sadeghi (E-Journal of Chemistry)
A new and efficient one-pot synthesis of dihydropyridones derivatives by four-component reaction between cyanoacetamide, aryl aldehydes, and ethyl acetoacetate with ammonium acetate using nano ZnO is described. The reaction was performed in ethanol under reflux conditions and afforded good yields of products.